The Effect of Education Program on Knowledge and Self-Care Ability in Patients Undergoing Coronary Artery Bypass Grafting - Mansin, Anutsara; Lerdkittikulyotin, Supaluk; Lerttraikul, Nantiya; Asdornwised, Usavadee; Thanakiatpinyo, Thanitta; Tantiwongkosri, Kriangkrai (Nursing Science Journal of Thailand, 2016)
Purpose: The purpose of this study was to investigate the effect of an educative program on knowledge and self-care ability in patients undergoing Coronary Artery Bypass Graft (CABG) surgery. Design: A quasi-experimental design. Methods: The sample was composed of 100 patients who underwent CABG surgery for the first time. The first 49 patients were assigned into the control group, followed by 51 patients into the experimental group. The experimental group received the education program at the day appointed for a surgery, the day of admission, and the 5th post operative day. The education content was the comprehensive pre- and post-operative information enhancing recovery during hospitalization and at home delivered by giving verbal information with video. Data were collected by using the pre-operative and pre-discharge knowledge questionnaires and the self-care ability questionnaire, at the 5th day and the first month post operation. Data were analyzed by using mean, standard deviation, and independent t-test for test of difference between groups. Main findings: The study revealed that the pre-operative and pre-discharge knowledge mean scores, and the mean self-care ability scores at post-operative day 5th and at 1 month of the experimental group were significantly higher than those of the control group (p < .001). Conclusion and recommendations: The results suggest that the comprehensive education program should deliver by giving verbal information with video at the appropriate time, before surgery, the day of admission, post-operation and before discharge. ผลของโปรแกรมการสอนต่อความรู้และความสามารถในการดูแลตนเองในผู้ป่วยที่ได้รับ การผ่าตัดทำทางเบี่ยงหลอดเลือดแดงโคโรนารี่ บทคัดย่อ วัตถุประสงค์: เพื่อศึกษาผลของโปรแกรมการสอนต่อความรู้ ความสามารถในการดูแลตนเอง ในผู้ป่วยที่ได้รับการผ่าตัดทำทางเบี่ยงหลอดเลือดแดงโคโรนารี่ รูปแบบการวิจัย: การวิจัยกึ่งทดลอง (a quasi-experimental design) วิธีดำเนินการวิจัย: กลุ่มตัวอย่างเป็นผู้ป่วยที่ได้รับการผ่าตัดทำทางเบี่ยงหลอดเลือดแดงโคโรนารี่เป็นครั้งแรกจำนวน 100 ราย โดยผู้ป่วย 49 รายแรกถูกจัดให้อยุ่ในกลุ่มควบคุม และ 51 รายต่อมาอยู่ในกลุ่มทดลอง กลุ่มทดลองได้รับโปรแกรมการสอนเพื่อนัดหมายในวันที่มาผ่าตัด และวันที่มาผ่าตัด และหลังผ่าตัดวันที่ 5 เนื้อหาการสอนครอบคลุมความรู้ในระยะก่อนและหลังผ่าตัดเพื่อการฟื้นตัวที่โรงพยาบาลและบ้าน ด้วยวิธีการสอนแบบบรรยายร่วมกับสื่อวีดิทัศน์ รวบรวมข้อมูลด้วยแบบสอบถามความรู้ก่อนผ่าตัดและก่อนกลับบ้าน แบบสอบถามความสามารถในการดูแลตนเองหลังผ่าตัด วันที่ 5 และ 1 เดือน วิเคราะห์ข้อมูลทางสถิติด้วยค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน เปรียบเทียบความแตกต่างระหว่าง 2 กลุ่ม ด้วยสถิติทีอิสระ t (independent t-test) ผลการวิจัย: ผลการศึกษาพบว่า คะแนนเฉลี่ยความรู้ก่อนผ่าตัดและก่อนกลับบ้าน คะแนนเฉลี่ยความสามารถในการดูแลตนเองหลังผ่าตัดวันที่ 5 และ 1 เดือน ในกลุ่มทดลองมีมากกว่ากลุ่มควบคุมอย่างมีนัยสำคัญทางสถิติ (p < .001) สรุปและข้อเสนอแนะ: จากผลการวิจัยแสดงให้เห็นว่า โปรแกรมการสอนควรมีเนื้อหาความรู้อย่างครอบคลุมครบถ้วน ด้วยวิธีบรรยายร่วมกับสื่อวีดิทัศน์ในเวลาที่เหมาะสมก่อนผ่าตัด วันที่มาผ่าตัด ภายหลังผ่าตัด และก่อนกลับบ้าน คำสำคัญ: โปรแกรมการสอน ความรู้ ความสามารถในการดูแลตนเอง ทางเบี่ยงหลอดเลือดแดงโคโรนารี่